IDH2 deficiency accelerates skin pigmentation in mice via enhancing melanogenesis - Jung Hyun Park (Redox Biology, 2018)
Melanogenesis is a complex biosynthetic pathway regulated by multiple agents, which are involved in the production, transport, and release of melanin. Melanin has diverse roles, including determination of visible skin color and photoprotection. Studies indicate that melanin synthesis is tightly linked to the interaction between melanocytes and keratinocytes. α-melanocyte-stimulating hormone (α-MSH) is known as a trigger that enhances melanin biosynthesis in melanocytes through paracrine effects. Accumulated reactive oxygen species (ROS) in skin affects both keratinocytes and melanocytes by causing DNA damage, which eventually leads to the stimulation of α-MSH production. Mitochondria are one of the main sources of ROS in the skin and play a central role in modulating redox-dependent cellular processes such as metabolism and apoptosis. Therefore, mitochondrial dysfunction may serve as a key for the pathogenesis of skin melanogenesis. Mitochondrial NADP+-dependent isocitrate dehydrogenase (IDH2) is a key enzyme that regulates mitochondrial redox balance and reduces oxidative stress-induced cell injury through the generation of NADPH. Downregulation of IDH2 expression resulted in an increase in oxidative DNA damage in mice skin through ROS-dependent ATM-mediated p53 signaling. IDH2 deficiency also promoted pigmentation on the dorsal skin of mice, as evident from the elevated levels of melanin synthesis markers. Furthermore, pretreatment with mitochondria-targeted antioxidant mito-TEMPO alleviated oxidative DNA damage and melanogenesis induced by IDH2 deficiency both in vitro and in vivo. Together, our findings highlight the role of IDH2 in skin melanogenesis in association with mitochondrial ROS and suggest unique therapeutic strategies for the prevention of skin pigmentation. Keywords: Melanogenesis, α-MSH, IDH2, Mitochondria, Mito-TEMPO